2005
DOI: 10.17816/ecogen345-10
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oil pollution on morphology and cytogenetic characteristics of plants

Abstract: Height stimulation and inhibition the flowering, formation of seeds and germination capacity is observed in the regions highly polluted with products of combustion and domestic cottage processing of oil. At the same time the level of chromosome aberration increase significantly in root meristema of seedlings of these plants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The results of the study confirm the opinion that, in comparison with other test biological objects show the greatest sensitivity to soil contamination with oil pollutants (Nikitina 2003). Decrease in germination of seeds of higher plants under the impact of hydrocarbons is also shown in the research works of other authors (Dzhambetova 2005). It was found that the content of hydrocarbons in the medium reduces the radish germination, seed germination in coniferous wood plants (Donets 2009).…”
mentioning
confidence: 60%
“…The results of the study confirm the opinion that, in comparison with other test biological objects show the greatest sensitivity to soil contamination with oil pollutants (Nikitina 2003). Decrease in germination of seeds of higher plants under the impact of hydrocarbons is also shown in the research works of other authors (Dzhambetova 2005). It was found that the content of hydrocarbons in the medium reduces the radish germination, seed germination in coniferous wood plants (Donets 2009).…”
mentioning
confidence: 60%
“…R the similar work was carried out in the most polluted settlements, where dozens of mini-plants were located. The level of soil contamination by oil products and genotoxicity of contaminated soils were studied using the same species T. officinale [5]. Table IV shows the concentrations of oil products and benz(a)pyrene in soils during the existence of mini factories and after their liquidation.…”
Section: B Oil Productsmentioning
confidence: 99%
“…Of particular interest are the in situ studies carried out on plants, naturally living in contaminated areas, and plant test-systems. The influence of radiation accidents [1,2], heavy metal pollution [3,4], pesticides and oil products [5][6][7], industrial enterprises [8], as well as the conditions of urban areas [9][10][11] was studied using these methods.…”
Section: Introductionmentioning
confidence: 99%